Elucidation Of Structure - Function Relationship In Families Of Copper Binding Proteins In Homo Sapiens – A Bioinformatics Approach - MATHANGI JAYARAMAN,; SUDARSHANA N,; VIDYA NATARAJAN,; UMASHANKAR VETRIVEL,; SULOCHANA. K.N, (International Journal of Pharma and Bio Sciences, 2012)
Copper is one of the important trace metals used in a multitude of cellular activities including respiration, angiogenesis and generation of immune responses. Its homeostasis is strictly orchestrated by copper binding proteins which include structural membrane proteins, intracellular enzymes and copper chaperones. Apart from serving as an important co-factor in various enzymes, copper plays a vital role in triggering normal and tumor angiogenesis, the latter resulting in metastasis. Hence, curbing excess copper levels is the key to designing antiangiogenic, anticancer therapies. This evokes the need for a better understanding of copper binding proteins. This study presents a systematic classification of copper binding proteins. The binding domain within and across various copper binding protein families has been analysed. The importance of two highly conserved residues in the binding pocket namely cysteine and histidine have been discussed. The detailed study revealed the possibility of designing an antiangiogenic peptide based on conserved histidines present in the LOX family of enzymes.